2021
DOI: 10.1530/edm-20-0196
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in multiple endocrine neoplasia type 1 (MEN1)

Abstract: Summary A 38-year-old female was identified as carrying a heterozygous pathogenic MEN1 variant (c.1304delG) through predictive genetic testing, following a diagnosis of familial hyperparathyroidism. Routine screening for parathyroid and pituitary disease was negative. However, cross-sectional imaging by CT revealed a 41 mm pancreatic tail mass. Biopsy via endoscopic ultrasound confirmed the lesion to be a well-differentiated (grade 1) pancreatic neuroendocrine tumour (pNET) with MIB1<1%. Biochemically, hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Jeong et al described a case where a previously healthy 45-year-old woman presented MEN-1 symptoms first through a breast mass [ 13 ]. Cheah et al discussed a woman in her thirties with MEN-1 who developed a histologically confirmed ductal breast tumor [ 14 ]. Notably, most reported cases in young women were also histologically ductal.…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al described a case where a previously healthy 45-year-old woman presented MEN-1 symptoms first through a breast mass [ 13 ]. Cheah et al discussed a woman in her thirties with MEN-1 who developed a histologically confirmed ductal breast tumor [ 14 ]. Notably, most reported cases in young women were also histologically ductal.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, it has been proposed that the risk of breast carcinoma is heightened in females with MEN1. To date, there have been approximately 90 or fewer cases of breast carcinoma in women with MEN1 reported in the literature (24,43,44,51,72,81,87,95,99,(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150); breast cancer has not yet been reported in a man with MEN1. The exact number of cases is difficult to determine due to the likely overlap of cases in the published literature and the lack of specific case numbers in one publication.…”
Section: Breast Carcinomamentioning
confidence: 99%
“…MEN1 pathogenic variants in exon 2, 9, and 10 are prone to a more aggressive pancreatic NET behavior [ 72 ]. Other nonendocrine components have been placed in relationship with MEN1 like breast cancer or melanoma, but currently, there is insufficient statistical evidence to directly connect them with the MEN1-associated picture [ 89 , 90 ].…”
Section: Introductionmentioning
confidence: 99%